The Learning Strategy of Islamic Education in Upgrade of Learning Quality - Dinil Abrar Sulthani (Pusat Penerbitan Universitas (P2U) Unisba, 2017)
AbstractThis study is attempted to reveal, analyze, and investigate the learning strategies practiced by the teachers of Islamic study in teaching the materials in Islamic senior high school of Al-Azhar 1 Jakarta. The instruments used in this study were 1) observation, 2) interview, and 3) documentation. The findings were elaborated into categorization, description, analysis, and recommendation. Based on the findings, the learning strategy applied in Islamic senior high school Al-Azhar 1 Jakarta is by selecting of learning strategies and then mixing them. The learning strategies were direct learning strategy, indirect learning strategy, interactive learning strategy, learning strategy through experience and independent learning strategy. Those strategies are the success factors of learning in the school, especially for Islamic study. Therefore, the teaching learning in Islamic Senior High School Al-Azhar 1 Jakarta needs to upgrade its quality and the teachers of Islamic Education should develop the various learning strategies.Keywords: Learning strategies, teachers, learners. Abstrak Penelitian ini dilakukan untuk mengungkap, menganalisis, dan menjelaskan strategi pembelajaran yang digunakan guru agama Islam dalam menyampaikan materi pelajaran di SMA Islam Al-Azhar 1 Jakarta. Instrumen yang digunakan dalam penelitian di lokasi penelitian yaitu 1) observasi, 2) wawancara, dan 3) studi dokumentasi. Data yang ditemukan di lokasi penelitian, selanjutnya penulis mengkategorisasi, mendeskripsikan, dan menganalisis, serta memberikan rekomendasi atas hasil yang ditemukan. Berdasarkan penelitian yang telah dilakukan bahwa strategi pembelajaran yang diterapkan di SMA Islam Al-Azhar 1 Jakarta adalah memilih dan menggabungkan beberapa strategi pembelajaran seperti; strategi pembelajaran langsung, strategi pembelajaran tidak langsung, strategi pembelajaran interaktif, strategi pembelajaran melalui pengalaman dan strategi pembelajaran mandiri. Strategi pembelajaran tersebut merupakan salah satu faktor keberhasilan pembelajaran di sekolah, secara khusus pelajaran agama Islam. Dengan demikian, pelaksanaan pembelajaran di SMA Islam Al-Azhar 1 Jakarta agar meningkatkan kualitasnya, dan guru PAI melakukan pengembangan strategi pembelajaran secara variatif. Kata kunci: Strategi pembelajaran, guru, peserta didik.